Respuestas
Respuesta dada por:
1
Respuesta:
1/3 [x² sen(3x) + 2/3 x cos(3x) - 2/27 sen(3x)]
Explicación paso a paso:
∫x² . cos(3x) dx = u . v - ∫ u´. v . dx
- Por partes: u = x²; u´= 2x; v´= cos(3x) ; v = 1/3 sen(3x)
x² . 1/3 sen(3x) - ∫2x . 1/3 sen(3x) =
x² . 1/3 sen (3x) - 2/3 ∫x . sen(3x) =
- Nuevamente por partes: u = x; u´= 1; v´= sen(3x) ; v = -1/3 cos(3x)
x² . 1/3 sen(3x) -2/3 [ x . (-1/3 cos(3x)) - ∫1 .(- 1/3 cos(3x))] =
x² . 1/3 sen(3x) - 2/3 [ -x . 1/3 cos(3x) + 1/3 ∫cos(3x)] =
x² . 1/3 sen(3x) - 2/3 [ -x . 1/3 cos(3x) + 1/3 . 1/3 sen(3x)] =
x² . 1/3 sen(3x) + x . 2/9 cos(3x) - 2/27 . sen(3x) =
1/3 x² sen(3x) + 2/9 x cos(3x) - 2/27 . sen(3x) =
1/3 [x² sen(3x) + 2/3 x cos(3x) - 2/27 sen(3x)]
Respuesta dada por:
0
Respuesta:
[3(cos12⁰+icos12⁰)]⁰
Preguntas similares
hace 5 años
hace 5 años
hace 7 años
hace 7 años
hace 9 años
hace 9 años